Race and class in big data - Harper, Logan; Culver, Daniel A; Cozier, Yvette C (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Social determinants of health are well-established drivers of health outcomes across a range of pulmonary diseases, from asthma to COPD to sarcoidosis. Developing interventions to address health disparities in pulmonary disease has been complicated by the wide-reaching and varied effects of structural racism and classism. In this issue of Sarcoidosis, Vasculitis, and Diffuse Lung Diseases, Cherabuddi and colleagues present data on the effect of a range of socio-economic factors impacting access to care in sarcoidosis. This work investigates a range of potential drivers of disparity, providing valuable information regarding potential interventional targets.[...]